Perspectives on the popularization of smart senior care to meet the demands of older adults living alone in communities of Southwest China: A qualitative study - Kong, Dehui; Liu, Siqi; Hong, Yan; Chen, Kun; Luo, Yu (Frontiers in Public Health, 2023)
Background Older adults who live alone face challenges in daily life and in maintaining their health status quo. Currently, however, their growing demands cannot be satisfied with high quality; therefore, these demands expressed by elders may be settled in the form of smart senior care. Hence, the improvement in smart senior care may produce more positive meanings in promoting the health and sense of happiness among this elderly population. This study aimed to explore the perceptions of demands and satisfaction with regard to the provision of senior care services to the community-dwelling older adults who live alone in Southwest China, thus providing a reference for the popularization of smart senior care. Methods This study adopted a qualitative descriptive approach on demands and the popularization of smart senior care. Semi-structured and in-depth individual interviews were conducted with 15 community-dwelling older adults who lived alone in Southwest China between March and May 2021. Thematic analysis was applied to analyze the data. Results Through data analysis, three major themes and subcategories were generated: “necessities” (contradiction: more meticulous daily life care and higher psychological needs vs. the current lower satisfaction status quo; conflict: higher demands for medical and emergency care against less access at present), “feasibility” (objectively feasible: the popularization of smart devices and applications; subjectively feasible: interests in obtaining health information), and “existing obstacles” (insufficient publicity; technophobia; patterned living habits; and concerns). Conclusions Smart senior care may resolve the contradiction that prevails between the shortage of medical resources and the increasing demands for eldercare. Despite several obstacles that stand in the way of the popularization of smart senior care, the necessities and feasibility lay the preliminary foundation for its development and popularization. Decision-makers, communities, developers, and providers should cooperate to make smart senior care more popular and available to seniors living alone, facilitating independence while realizing aging in place by promoting healthy aging.